PENGEMBANGAN SISTEM PENCIUMAN ELEKTRONIK DENGAN 16 BUAH SENSOR KUARSA DAN ALGORITMA NEURAL PROPAGASI BALIK UNTUK PENGENALAN AROMA CAMPURAN - Kusumoputro, Benyamin; Jatmiko, Wisnu (UI Scholars Hub, 2002)
An artificial odor recognition system is developed for discriminating odors. This artificial system consisted of 16 quartz resonator crystals as the sensor array, a frequency modulator and a frequency counter for each sensor that are connected directly to a microcomputer. We have already shown that the artificial odor recognition system with 4 sensors is high enough to discriminate simple odor correctly, however, when it was used to discriminate compound odors, the recognition capability of this system is dropped significantly to be about 40%. Results of experiments show that the developed artificial system with 16 sensors could discriminate compound aroma based on 6 gradient of alcohol concentrations with high recognition rate of 89.9% for non batch processing system, and 82.4% for batch processing of the classes of odors